Health Communication and the HIV Continuum of Care. (1st January 2017) - Vermund, Sten H.; Mallalieu, Elizabeth C.; Van Lith, Lynn M.; Struthers, Helen E.
Abstract : Abstract: Health communication is a broad term that applies to the fundamental need for practitioners, policy makers, patients, and community members to understand one another around health promotion and health care issues. Whether in a consultation between nurse and patient, a health clinic director's engagement with the health ministry, or a community campaign for encouraging HIV testing, all have critical health communication elements. When people's needs are not perceived by them to be addressed or clients/patients do not understand what is being communicated, they are unmotivated to engage. Health communication may be deployed at multiple levels to encourage positive behavior change and affect HIV treatment outcomes. As countries move to treatment for all as soon as possible after testing, health communication can help address significant losses at each stage of the HIV continuum of care, thereby contributing to achieving the 90-90-90 global treatment goals. This JAIDS supplement presents compelling studies that are anchored on the health communication exigencies in highly diverse HIV and AIDS contexts in low and middle income settings. Our special focus is health communication needs and challenges within the HIV continuum of care. We introduce the supplement with thumbnails summaries of the work presented by an experienced array of public health, behavioral, and clinical scientists.